Discursos de consultores sobre acreditação hospitalar - Breno Augusto Duarte Roberto (2019)
This is a qualitative study, outlined by the discourse analysis research method, with the purpose of examining the speeches of certifiable management systems consultants for hospital accreditation, considering the interactions experienced between these professionals and the client organizations. This study was developed in a consulting firm specialized in health sector, based in Belo Horizonte but with a national scope, present in the market for 25 years and responsible for the management restructuring of more than 200 organizations and has conducted more than 100 certifications. The participants were consultants hired by this company, from different academic backgrounds, being ten nurses, one Biomedical graduate and one Law graduate, adding up to twelve professionals. Data collection was done through interviews using a semi-structured script. The interviews were understood through discourse analysis. First, systematic readings of the speeches portrayed in the interviews were made and transformed into notes of reflection. Then, the crossing of these reflections allowed the construction of the categories. The data were organized into three categories and their subcategories: 1. The daily practice of consulting; 2.1 Difficulties experienced during the consulting routine; 2.2 Discontinuation of the accreditation process. 3. Expectation versus reality of hospital accreditation. The results of the study show what the consultants understand about the activity they perform within hospitals, as well as the difficulties these professionals face in implementing accreditation and what functions are required to be performed in order to succeed in the implementation project. It was also observed that there may be a misalignment between what is expected from hospital accreditation, built from the discourse disseminated in society, and the results achieved with the implementation of this method. This research is expected to contribute to increasing the knowledge of how hospital accreditation occurs, from the perspective of the consultants, thus enabling a broader approach on the subject as well as increasing the understanding of both the factors that facilitate and hinder the implementation and maintenance of accreditation practices.